2019
DOI: 10.1253/circj.cj-19-0187
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Acute Myocardial Infarction Incidence and Mortality Between 2006 and 2016 in Tokyo ― Report From the Tokyo CCU Network ―

Abstract: Background: Temporal trends in the incidence and mortality of acute myocardial infarction (AMI) have not been fully clarified in Japan. Methods and Results: The Tokyo CCU network collects information every 3 months regarding the number of AMI cases, age of patients and in-hospital mortality. Age-adjusted hospitalized AMI numbers were unchanged from 2006 to 2016 (40.7/100,000 persons/year in 2016). Annual age-adjusted in-hospital mortality decreased slightly (5.8% in 2006 to 5.2% in 2016). Conclusions: A steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 15 publications
3
32
3
Order By: Relevance
“…Therefore, it can be inferred that the improvement in the analytic performance of troponin assays and the change of definition for AMI are among the causes for the trend seen in the incidence rate. Our inference is convincing because recent trends in the incidence of AMI in other countries6782425 tend to be similar to that seen in this study. Some studies have shown a large decrease in the incidence rate before 2010 or 2011; however, thereafter the incidence rate has shown a relatively small decrease or has remained steady 345.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, it can be inferred that the improvement in the analytic performance of troponin assays and the change of definition for AMI are among the causes for the trend seen in the incidence rate. Our inference is convincing because recent trends in the incidence of AMI in other countries6782425 tend to be similar to that seen in this study. Some studies have shown a large decrease in the incidence rate before 2010 or 2011; however, thereafter the incidence rate has shown a relatively small decrease or has remained steady 345.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies have shown a large decrease in the incidence rate before 2010 or 2011; however, thereafter the incidence rate has shown a relatively small decrease or has remained steady 345. Studies from Singapore,6 Poland25 and Japan8 have reported a slight increase in the rates again from 2011, like in this study. Despite the effect of introduction of hs-cTn and the new definition of AMI, Korean health providers should change the preventive strategies to decrease the incidence of AMI as it has remained steady since 2011.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The details of the Tokyo CCU Network Registry have been described elsewhere. 8, 15 TTS was diagnosed based on the revised Mayo Clinic criteria 16 by attending physicians at 71 participating acute cardiovascular care hospitals. Because data on BT started to be collected in the registry from 2013, data on patients hospitalised with TTS from January 2013 to December 2015 were used for the present study.…”
Section: Methodsmentioning
confidence: 99%
“…High BT was defined according to the World Health Organization’s definition of fever. 17 As there is no generally accepted definition of hypothermia on the basis of axillary temperature, 1820 we defined low BT as an axillary temperature below 36.0°C in this study.…”
Section: Methodsmentioning
confidence: 99%